2010
DOI: 10.5194/aab-53-130-2010
|View full text |Cite
|
Sign up to set email alerts
|

Variations in feeding behaviour of high-yielding dairy cows in relation to parity during early to peak lactation

Abstract: The objective of this study was to compare the feeding behaviour of high-yielding dairy cows in relation to parity during early to peak lactation and to determine whether or not there was any relationship between variables describing their feeding behaviour and total feed intake. Information concerning feed intake of each individual dairy cow is especially valuable for the herd management, particularly in early lactation. However, technical requirements for implementation are rarely given. Therefore, relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
7
6
1
Order By: Relevance
“…The PMR eating rate found in our study was higher than that found in the study by Bach et al (2007), in which cows were given a high concentrate allowance. However, the result of eating rate in our study was comparable with other studies with a similar stocking density at the feed bins (Azizi et al, 2010;. Thus, a tight time budget might exist because the cows in our study might have increased their eating rate due to limited time for eating (Nielsen, 1999) because of the rather high stocking density.…”
Section: Behavioral Responsessupporting
confidence: 84%
“…The PMR eating rate found in our study was higher than that found in the study by Bach et al (2007), in which cows were given a high concentrate allowance. However, the result of eating rate in our study was comparable with other studies with a similar stocking density at the feed bins (Azizi et al, 2010;. Thus, a tight time budget might exist because the cows in our study might have increased their eating rate due to limited time for eating (Nielsen, 1999) because of the rather high stocking density.…”
Section: Behavioral Responsessupporting
confidence: 84%
“…The conducted regression analyses verified these estimations with high significant (P<0.001) results (R²=0.8). These results show stronger correlations then published in previous studies (Azizi et al 2010, Kaufmann et al 2007. Differences can be caused by the use of DM intake in the cited studies while we used fresh matter intake as dependend variable.…”
Section: Discussionsupporting
confidence: 74%
“…Therefore, the differences we observed in traits associated with visits may disappear if the same analysis was performed on the basis of meals. Recent studies showed that eating rate was affected by animal characteristics such as parity (Azizi et al, 2009 and, MY level (Azizi et al, 2009), lactation stage (Abrahamse et al, 2008;Azizi et al, 2010) and diet composition (Baumont, 1996;Friggens et al, 1998;Abrahamse et al, 2008). Thus, in our study, we observed that eating rate could be affected by the haplotype at one QTL-F-Fert-BTA3.…”
Section: Discussionsupporting
confidence: 60%